Xanthogranulomatous orchitis after blunt testicular trauma mimicking a testicular tumor: A case report and comparison with published cases - Yamashita, Shimpei; Umemoto, Hidetoshi; Kohjimoto, Yasuo; Hara, Isao (Urology Journal, 2017)
Xanthogranulomatous orchitis has been reported to be an extremely rare inflammatory change caused by infection and is difficult to distinguish from testicular tumor. We report a 28-year-old man who presented with a lump in his left testis after a blunt testicular trauma. Based on a series of imaging tests, we suspected benign tumor such as epidermoid cyst and performed tumor enucleation (testis-sparing surgery) on the patient. Histopathological findings showed xanthogranulomatous orchitis. It is assumed that xanthogranulomatous orchitis in this case was caused by blunt testicular trauma and this is the first successful case of xanthoglomatous orchitis in salvaging the testis.